Battling absorptive losses by plasmon–exciton coupling in multimeric nanostructures. Issue 66 (19th July 2015) - Rahimi Rashed, Alireza; De Luca, Antonio; Dhama, Rakesh; Hosseinzadeh, Arash; Infusino, Melissa; El Kabbash, Mohamed; Ravaine, Serge; Bartolino, Roberto; Strangi, Giuseppe
<x xml:space="preserve">Abstract</x> This study presents a novel approach dealing with absorptive losses in plasmonic metamaterials, capitalizing on field enhancement effect in multimeric nanostructures.